2001
DOI: 10.1046/j.1523-1755.2001.00727.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of parvovirus B19 infection with idiopathic collapsing glomerulopathy

Abstract: The significantly higher prevalence of PVB19 DNA in renal biopsies and peripheral blood of CG patients suggests a specific association between PVB19 infection and CG. In susceptible individuals, renal epithelial cell infection with PVB19 may induce CG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
108
1
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(118 citation statements)
references
References 34 publications
(7 reference statements)
3
108
1
6
Order By: Relevance
“…The pathologic variants and percentage of sclerotic glomeruli were also comparable between the two groups. These findings indicated that IgM deposition is not likely the initiation of FSGS lesion, which has been identified as several genes mutations or variants (9-13), circulating permeability factors (14)(15)(16), and others (17)(18)(19)(20)(21)(22)(23). However, IgM and complement-mediated injury may be secondary phenomena that occur after the primary renal insult.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The pathologic variants and percentage of sclerotic glomeruli were also comparable between the two groups. These findings indicated that IgM deposition is not likely the initiation of FSGS lesion, which has been identified as several genes mutations or variants (9-13), circulating permeability factors (14)(15)(16), and others (17)(18)(19)(20)(21)(22)(23). However, IgM and complement-mediated injury may be secondary phenomena that occur after the primary renal insult.…”
Section: Discussionmentioning
confidence: 97%
“…The eGFR was calculated with the Modification of Diet in Renal Disease Study equation adjusted for the Chinese population: eGFR=1753(serum creatinine) 21.234 3 age 20.179 30.79 (if a woman) (6).…”
Section: Patientsmentioning
confidence: 99%
“…Complex genetic factors are undoubtedly critical to the development of non-Mendelian podocyte disease, including disease triggered by environmental factors. It has been suggested, for example, that parvovirus infection is associated with the development of FSGS (99,100). HIV infection is associated with a distinct podocytopathy (see review by Ross and Klotman in this issue [101]).…”
Section: Sporadic Fsgsmentioning
confidence: 99%
“…FSGS affects African Americans to a disproportionate extent. FSGS may be associated with viral infections, including HIV-1 (20) and possibly parvovirus B19 (21,22).…”
mentioning
confidence: 99%